Audiomotor Integration in Minimally Conscious State: Proof of Concept!. (3rd September 2015) - Naro, Antonino; Leo, Antonino; Cannavò, Antonino; Buda, Antonio; Bruno, Rocco; Salviera, Carlo; Bramanti, Placido; Calabrò, Rocco Salvatore
Abstract : Patients suffering from chronic disorders of consciousness (DOC) are characterized by profound unawareness and an impairment of large-scale cortical and subcortical connectivity. In this study, we applied an electrophysiological approach aimed at identifying the residual audiomotor connectivity patterns that are thought to be linked to awareness. We measured some markers of audiomotor integration (AMI) in 20 patients affected by DOC, before and after the application of a repetitive transcranial magnetic stimulation protocol (rTMS) delivered over the left primary motor area (M1), paired to a transauricular alternating current stimulation. Our protocol induced potentiating of the electrophysiological markers of AMI and M1 excitability, paired to a clinical improvement, in all of the patients with minimally conscious state (MCS) but in none of those suffering from unresponsive wakefulness syndrome (UWS). Our protocol could be a promising approach to potentiate the functional connectivity within large-scale audiomotor networks, thus allowing clinicians to differentiate patients affected by MCS from UWS, besides the clinical assessment.